2021
DOI: 10.1093/ajcn/nqaa284
|View full text |Cite
|
Sign up to set email alerts
|

Replacing the consumption of red meat with other major dietary protein sources and risk of type 2 diabetes mellitus: a prospective cohort study

Abstract: Background Greater consumption of red meat has been associated with a higher risk of type 2 diabetes mellitus (T2DM). A decreased intake of red meat and simultaneous increased intake of other high-protein foods may be associated with a lower risk of T2DM. These analyses of specific food replacements for red meat may provide more accurate dietary advice. Objective We examined the association between a decrease in intake of red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…Such initiatives are likely to be most effective in the U.S., where red meat intake is high. One study conducted in 2019 reported that T2DM incidence decreased when red meat was substituted with poultry (HR: 0.96, 95% CI 0.93, 0.99) or fish (HR: 0.94, 95% CI 0.91, 0.97) [51], and, recently, a cohort study including 148,853 participants found that replacing red meat consumption (both PRM and URM) with other protein sources (poultry, seafood, egg, legumes and nuts) was associated with a lower risk of T2DM, and stronger for the replacement of PRM [57]. Further research is demanded to explore the effect of a decreased intake of red meat and simultaneous increased intake of other high-protein foods on diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Such initiatives are likely to be most effective in the U.S., where red meat intake is high. One study conducted in 2019 reported that T2DM incidence decreased when red meat was substituted with poultry (HR: 0.96, 95% CI 0.93, 0.99) or fish (HR: 0.94, 95% CI 0.91, 0.97) [51], and, recently, a cohort study including 148,853 participants found that replacing red meat consumption (both PRM and URM) with other protein sources (poultry, seafood, egg, legumes and nuts) was associated with a lower risk of T2DM, and stronger for the replacement of PRM [57]. Further research is demanded to explore the effect of a decreased intake of red meat and simultaneous increased intake of other high-protein foods on diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, eating white potatoes with eggs appears to control glycemic response [112]. There is an increasing prevalence of obesity and DM in the US during these decades [113,114]. The different responses to egg consumption between the US and other countries are probably attributable to residual confounding by dietary behaviors or food preparation methods restricted to certain populations.…”
Section: Egg and Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…Choline is listed up in US dietary guidelines as an essential nutrient, but not in Japan, and egg, milk and meat are the major sources of choline not only in the US but in Western diets. Replacing red meat consumption with other protein sources, including egg, was associated with a lower risk of T2DM in US cohorts [114] (refer section of "Debates around Trimethylamine Oxide"). However, it is not clear at present whether this mechanism is also responsible for cases in other Western countries.…”
Section: Egg and Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…In terms of HbA 1c , we found that after adjustment for weight change, no associations of replacement of processed meat with other foods showed significance. However, Würtz et al [14] reported that the association of replacement of red meat with both plant-and animal-based foods with risk of type 2 diabetes was independent of weight change in 3 US prospective cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Animal-based foods have recently been connected to worsened metabolic outcomes and emerging epidemiological evidence suggests that red and processed meat intake is associated with an increased risk of weight gain [8], type 2 diabetes [9], and CVD [10e12]. Prospective cohort studies show that replacing red meat with other foods such as nuts and grains is associated with a lower risk of type 2 diabetes and CVD [10,13,14]. Regarding other animal-based foods including dairy products, poultry, fish and seafood, and eggs, null or conflicting findings have been reported [8,15e18].…”
Section: Introductionmentioning
confidence: 99%